Blended Learning Management in Madrasah Tsanawiyah During Covid-19 Pandemic - Abdullah Syahid Royyan; Supadi Supadi; Fakhrudin Arbah (Universitas Pendidikan Mandalika, 2023)
This research aims to analyze the concept of blended learning management that has been applied to Madrasah Tsanawiyah during the Covid-19 Pandemic. The research method used was qualitative, using the CIPP model evaluation method (context, input, process, and product). The study was carried out at MTs Umdatur Rasikhien Jakarta. The purposive sampling technique was used in selecting the samples. Fifty people attended, including principals, teachers, students, and administrative staff. Data collection techniques used observation, interviews, and documents. Data analysis in this study went through data reduction, data presentation, discussion, and conclusion. The study results showed that MTs Umdatur Rasikhien had very good and stable blended learning management. It was proven that during the Covid-19 pandemic, schools strengthened management systems, especially in ICT operations and human resources. Technology management, foundation, school management support, awareness among the blended learning system members, and technological infrastructure readiness have been developed systematically. Even though the use of the learning management system at the junior high school level was less familiar, the school made the preparations so that teachers and teachers could use LMS properly and parents could support students studying at home. Student learning outcomes were also stable, and 40% of students experience increased achievement. So, school management must pay attention to the concept of strength possessed by the school and current needs in providing education in any situation.